Učinek nalog, ki kratkotrajno izboljšajo delovanje živčno mišičnega sistema na ravnotežje - Čop, Katja (Šport (Ljubljana), 2019)
The aim was to compare the effects of three warm up protocols on postural control. Seventeen volunteers performed tandem stance with eyes closed (EC) pre- and post-warm up (0.5 min, 6 min and 12 min). Pre- and post-warm up, the displacement velocities and amplitudes of the center of pressure during tandem stance were assessed. Three different warm up protocols in randomized order were performed: (i) six minutes of low-intensity (20 cm, 60 to 65 % of maximal heart rate) stepping, (ii) six minutes of low-intensity stepping with additional plyometric conditioning activity, i.e., jumps (6 repetitions in 3 sets, 2.5 min inter-set rest) and (iii) six minutes of low-intensity stepping with additional maximal isometric conditioning activity (maximal leg extension, 3 repetitions in 5 to 8 s, 2.5 min inter-set rest). In comparison with pre-warm up, only low-intensity stepping with added plyometric conditioning activity improves the quality of performing the tandem stance with EC, probably due to increased sensitivity of muscle spindle. But 12 minutes of recovery are required to obtain postural control enhancement. On the other hand, low-intensity stepping with isometric conditioning activity diminished postural control. In conclusion, plyometric conditioning activity should precede balance exercise, particularly, when warm-up procedure consists of low-intensity whole body exercise.
Keywords: balance; post-activation potentation; post-aktivacijska potenciacija; ravnotežje; sport; šport; tandem stance; tandemska stoja